1989
DOI: 10.1111/j.1365-246x.1989.tb00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Reconstruction of 2-D Vector Fields: Application to Flow Imaging

Abstract: We examine the problem of reconstructing a 2-D vector field v(x, y ) throughout a bounded region D from the line integrals of v(x, y ) through D. This problem arises in the 2-D mapping of fluid-flow in a region D from acoustic travel-time measurements through D. For an arbitrary vector field, the reconstruction problem is in general underdetermined since v(x, y ) has two independent components, v,(x, y) and v,(x, y). However, under the constraint that v is divergenceless ( V -v = O ) in D , we show that the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
105
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 8 publications
3
105
0
Order By: Relevance
“…Several applications of vector field tomography have been considered in the literature. These include: blood flow imaging [4,5]; fluid mesoscale velocity imaging in ocean acoustic tomography [6][7][8]; fluid-flow imaging [9][10][11][12][13][14][15][16]; electric field imaging in Kerr materials [17][18][19]; imaging of the component of the gradient of the refractive index field, which is transversal to the beam, in Schlieren tomography [14]; velocity field imaging of heavy particles in plasma physics [20]; density imaging in supersonic expansions and flames in beam deflection optical tomography [21]; non-destructive stress distribution imaging of transparent specimens in photoelasticity [22,23]; determination of temperature distributions and velocity vector fields in furnaces [24]; and magnetic field imaging in Tokamak in polarimetric tomography [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several applications of vector field tomography have been considered in the literature. These include: blood flow imaging [4,5]; fluid mesoscale velocity imaging in ocean acoustic tomography [6][7][8]; fluid-flow imaging [9][10][11][12][13][14][15][16]; electric field imaging in Kerr materials [17][18][19]; imaging of the component of the gradient of the refractive index field, which is transversal to the beam, in Schlieren tomography [14]; velocity field imaging of heavy particles in plasma physics [20]; density imaging in supersonic expansions and flames in beam deflection optical tomography [21]; non-destructive stress distribution imaging of transparent specimens in photoelasticity [22,23]; determination of temperature distributions and velocity vector fields in furnaces [24]; and magnetic field imaging in Tokamak in polarimetric tomography [25].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, physical problems are often defined on bounded domains and it is the boundary that creates or partially defines the field. Norton [16,21], Braun and Hauck [20], and Osman and Prince [35] were all concerned about the vector field tomography problem on bounded domains. Norton showed that the longitudinal measurements with boundary conditions reconstruct a divergence-free vector field composed of a solenoidal component that satisfies homogeneous boundary conditions and an irrotational component defined by the gradient on the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…History of Vector Field Tomography Tensor tomography builds on much of the work already accomplished in vector field tomography [2,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. Applications have involved acoustic flow imaging using time-of-flight measurements in medicine [7], non-destructive evaluation [11], and ocean tomography [9,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations